Improving the Oral Bioavailability of an Anti-Glioma Prodrug CAT3 Using Novel Solid Lipid Nanoparticles Containing Oleic Acid-CAT3 Conjugates - Hongliang Wang; Lin Li; Jun Ye; Rubing Wang; Renyun Wang; Jinping Hu; Yanan Wang; Wujun Dong; Xuejun Xia; Yanfang Yang; Yue Gao; Lili Gao; et al. (MDPI AG, 2020)
13a-(S)-3-pivaloyloxyl-6,7-dimethoxyphenanthro(9,10-b)-indolizidine (CAT3) is a novel oral anti-glioma pro-drug with a potent anti-tumor effect against temozolomide-resistant glioma in vivo. However, poor lipid solubility has limited the encapsulation efficacy during formulation development. Moreover, although the active metabolite of CAT3, 13a(S)-3-hydroxyl-6,7-dimethoxyphenanthro(9,10-b)-indolizidine (PF403), can penetrate the blood-brain barrier and approach the brain tissue with a 1000-fold higher anti-glioma activity than CAT3 in vitro, its bioavailability and Cmax were considerably low in plasma, limiting the anti-tumor efficacy. In this study, a novel oleic acid-CAT3 conjugate (OA-CAT3) was synthesized at the first time to increase the lipid solubility of CAT3. The OA-CAT3 loaded solid lipid nanoparticles (OA-CAT3-SLN) were constructed using an ultrasonic technique to enhance the bioavailability and Cmax of PF403 in plasma. Our results demonstrated that CAT3 was amorphous in the lipid core of OA-CAT3-SLN and the in vitro release was well controlled. Furthermore, the encapsulation efficacy and the zeta potential increased to 80.65 ± 6.79% and −26.7 ± 0.46 mV, respectively, compared to the normal CAT3 loaded SLN. As indicated by the high-performance liquid chromatography-mass spectrometry (HPLC-MS/MS) quantitation, the monolayer cellular transepithelial transport rate of OA-CAT3-SLN improved by 2.42-fold relied on cholesterol compared to the CAT3 suspension. Hence, the in vitro cell viability of OA-CAT3-SLN in C6 glioma cells decreased to 29.77% ± 2.13% and 10.75% ± 3.12% at 48 and 72 h, respectively. Finally, compared to the CAT3 suspension, the in vivo pharmacokinetics in rats indicated that the plasma bioavailability and Cmax of PF403 as afforded by OA-CAT3-SLN increased by 1.7- and 5.5-fold, respectively. Overall, the results indicate that OA-CAT3-SLN could be an efficacious delivery system in the treatment of glioma.